HYBRIDIZATION AND THERMAL STABILITY EFFECTS ON PHYSICAL PROPERTIES OF HYBRID GLASS/JUTE FIBER REINFORCED EPOXY COMPOSITES - Mohamad, N.; Hassan, M.F.; Chang, S.Y.; Yuhazri, M.Y.; Abd Manaf, M.E.; Ab Maulod, H.E.; Razak, J.A.; Munawar, R.F.; Qumrul, A. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Incorporation of natural fibers with partial replacement of synthetic fibers leads to a new venture in composite tooling industries due to their recyclability limitation as well as potential for weight and cost reduction. This work compares the density and evaluates the effect of thermal cycles of 0, 1, 3, 7, 12, 20, 30 and 50 cycles at two different temperatures; i) 120°C and ii) 200°C to the physical properties of hybrid glass/jute fiber reinforced epoxy laminated composites. The composites were prepared via vacuum infusion working at a pressure of 100 kPa, soaking time of 120 minutes and with the use of flow media. The composite exposed to thermal cycles at 200°C exhibited lower density due to removal of volatile elements which lead to porous structures. It experienced higher weight loss from partial degradation of natural fibers at 200°C. The composite subjected to thermal cycle at 120°C showed stable physical properties even after 50 thermal cycles. The water absorption reflects the level of curing completeness, which varies with exposed temperature and number of thermal cycles. The findings indicate that the hybrid glass/jute fiber reinforced epoxy composite exhibits potential to be used as a tooling material with apparent weight reduction and dimensional stability under thermal effect.